2006
DOI: 10.1631/jzus.2006.b0844
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface EMG signals using improved approximate entropy

Abstract: An improved approximate entropy (ApEn) is presented and applied to characterize surface electromyography (sEMG) signals. In most previous experiments using nonlinear dynamic analysis, this certain processing was often confronted with the problem of insufficient data points and noisy circumstances, which led to unsatisfactory results. Compared with fractal dimension as well as the standard ApEn, the improved ApEn can extract information underlying sEMG signals more efficiently and accurately. The method introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In addition, the muscles under 40˝angle need more motor units to maintain and adjust the discharge of the muscle fibers or reinforces the shorter fibers [55], as a result, the firing of the motor units and the discharge of muscle fibers might be more complex than that under 180˝angle. The conclusion is consistently fitted with the literature as Chen et al [56] reported. This supports the hypothesis that the firing of the motor units and the discharge of the muscle fibers play a direct role in modulating the contraction of muscle groups to generate different motor patterns.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the muscles under 40˝angle need more motor units to maintain and adjust the discharge of the muscle fibers or reinforces the shorter fibers [55], as a result, the firing of the motor units and the discharge of muscle fibers might be more complex than that under 180˝angle. The conclusion is consistently fitted with the literature as Chen et al [56] reported. This supports the hypothesis that the firing of the motor units and the discharge of the muscle fibers play a direct role in modulating the contraction of muscle groups to generate different motor patterns.…”
Section: Discussionsupporting
confidence: 88%
“…Chaos is a complex motion which is always restricted in limited areas, extremely sensitive to initial values, long-term unpredictable, with track never repeated, fractal dimension and strange attractors. Amount of study demonstrated that Center Nervous System (CNS) generates chaotic firing patterns of action potentials; and a variety of physiological potential nerve signals, including EEG, ECG and EMG, etc., originated from CNS, have shown some degree of chaotic behavior, too [16][17][18][19][20][21][22][23][24][25][26][27][28]. Some nonlinear analysis methods are applied to the analysis of EMG.…”
Section: Chaotic Theory Analysis Methodsmentioning
confidence: 99%
“…This is done either by halfwave or full-wave rectification of the signal. A full-wave rectification method was applied to preserve the energy of the signal [25,[29][30][31][32][33][34], and the expression for the method is given in Eq. (1).…”
Section: Rectification Processmentioning
confidence: 99%
“…(2), where t j and t i denote the lower and upper bounds of the part of the signal to be integrated, respectively. The above expression represents the area below the absolute value of the signal curve at time T = t i -t j [30][31][32][33][34][35].…”
Section: Signal Energymentioning
confidence: 99%